THE EFFECT OF LOCALISED AND GLOBALISED FATIGUE ON CENTRE OF PRESSURE EXCURSIONS IN HEALTHY AND FUNCTIONALLY UNSTABLE PARTICIPANTS FOLLOWING A SINGLE LEG DROP JUMP LANDING; ANALYSING A SUBCONSCIOUS TIME PERIOD - Gautrey, C; Watson, T; Mitchell, A (British journal of sports medicine, 2014)
Background It has been reported that fatigue and stability deficits may be predispositions to musculoskeletal injury in functional ankle instability (FAI) sufferers. Analysis of subconscious time periods (initial 200 ms) may identify deficits in FAI sufferers that are not observed when analysing a conscious time frame. Objective To determine whether FAI participants suffer from subconscious neuromuscular deficits compared to healthy controls, as measured by COP excursion, following localised and globalised fatigue. Design Non-randomised experimental. Setting University biomechanics laboratory. Participants A convenience sample was used to recruit twenty males with unilateral FAI and twenty male healthy controls. Inclusion criteria included males, aged 18-25 years, who participated in semi-professional soccer and who were right leg dominant. Risk factor assessment Two localised fatigue protocols were investigated; isokinetic ankle inversion-eversion exercise and hip abduction-adduction exercise. Maximal repetitions were performed until three consecutive repetitions fell below 50% of participants 1RM. The soccer specific Drust protocol was used to elicit globalised fatigue. Three single leg drop jump landings from a 30 cm high bench onto a force platform were performed before and after fatigue. Subject group and fatigue protocols were the independent variables. Main outcome measure COP excursion in the anterior, posterior, anteroposterior, medial, lateral and mediolateral directions, following a single leg drop jump landing, before and after localised and globalised fatigue. Results The globalised soccer specific fatigue protocol caused the greatest significant increase (P<.0125) in medial, lateral and mediolateral excursion in both ankles of the FAI and healthy groups. The hip and ankle localised fatigue protocols found a significant increase (P<.0125) in COP excursion in the lateral and mediolateral directions in the FAI group alone. Conclusion Clinically, the results show that the fatigued individual may be at greater risk of injury, especially during more globalised prolonged exercise involving multiple joints, such as a simulated soccer protocol.